2022
DOI: 10.1186/s10020-022-00473-w
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota-testis axis: FMT improves systemic and testicular micro-environment to increase semen quality in type 1 diabetes

Abstract: Background Clinical data suggest that male reproductive dysfunction especially infertility is a critical issue for type 1 diabetic patient (T1D) because most of them are at the reproductive age. Gut dysbiosis is involved in T1D related male infertility. However, the improved gut microbiota can be used to boost spermatogenesis and male fertility in T1D remains incompletely understood. Methods T1D was established in ICR (CD1) mice with streptozotocin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 56 publications
0
30
0
Order By: Relevance
“…In the current study, RFX was applied to male infertility, exploiting the non-traditional action of RFX on microbiota, and providing an insight into gut-testes axis. Lately, modifying gut microbiome provided the curation of male infertility in T1D patients [69]. Regarding the mechanism of the action of RFX, preclinical and clinical studies provided evidence for anti-inflammatory and immune modulator effects [70].…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, RFX was applied to male infertility, exploiting the non-traditional action of RFX on microbiota, and providing an insight into gut-testes axis. Lately, modifying gut microbiome provided the curation of male infertility in T1D patients [69]. Regarding the mechanism of the action of RFX, preclinical and clinical studies provided evidence for anti-inflammatory and immune modulator effects [70].…”
Section: Discussionmentioning
confidence: 99%
“…Remodeling their GM by feeding melatonin or transplanting alginate oligosaccharides-improved fecal microbiota effectively alleviates the above conditions (Hao et al, 2022a;Sun et al, 2022). Zhang C. et al (2021), Zhang P. et al (2021), andHao et al (2022b) also found that transplantation of fecal microbiota from mice supplemented with alginate oligosaccharide to mice treated with busulfan or streptozotocin (a type 1 diabetes inducer) could rescue germ cell loss and improve semen quality through metabolic pathways. Although GM metabolites have an impact on fertility, basic phenomena yet remain to be defined completely.…”
Section: Discussionmentioning
confidence: 99%
“…Since diet is the most common route of human exposure to ZEN, whether the reproductive disorder caused by ZEN is potentially related with the microbiota in the gastrointestinal tract is a critical issue that needs to be studied. In recent years, research on the relationship between gut microbiota and organismal health has attracted worldwide attention, and there is growing evidence to support that the gut microbiota is closely related to reproductive health. ,, In the current study, we adopted high-throughput 16S rRNA sequencing to identify changes of gut microbiota induced by ZEN. Our results clearly showed that ZEN altered the composition of the gut microbiota and lead to a significant change in gut microbiota abundance in progeny of the ZEN-treated groups.…”
Section: Discussionmentioning
confidence: 99%